The Phenotypic Profile Associated With the FMR1 Premutation in Women: An Investigation of Clinical-Behavioral, Social-Cognitive, and Executive Abilities - Maltman, Nell; Guilfoyle, Janna; Nayar, Kritika; Martin, Gary E.; Winston, Molly; Lau, Joseph C. Y.; Bush, Lauren; Patel, Shivani; Lee, Michelle; Sideris, John; Hall, Deborah A.; Zhou, Lili; et al. (Frontiers in Psychiatry, 2021)
The FMR1 gene in its premutation (PM) state has been linked to a range of clinical and subclinical phenotypes among FMR1 PM carriers, including some subclinical traits associated with autism spectrum disorder (ASD). This study attempted to further characterize the phenotypic profile associated with the FMR1 PM by studying a battery of assessments examining clinical-behavioral traits, social-cognitive, and executive abilities in women carrying the FMR1 PM, and associations with FMR1-related variability. Participants included 152 female FMR1 PM carriers and 74 female controls who were similar in age and IQ, and screened for neuromotor impairments or signs of fragile X-associated tremor/ataxia syndrome. The phenotypic battery included assessments of ASD-related personality and language (i.e., pragmatic) traits, symptoms of anxiety and depression, four different social-cognitive tasks that tapped the ability to read internal states and emotions based on different cues (e.g., facial expressions, biological motion, complex social scenes), and a measure of executive function. Results revealed a complex phenotypic profile among the PM carrier group, where subtle differences were observed in pragmatic language, executive function, and social-cognitive tasks that involved evaluating basic emotions and trustworthiness. The PM carrier group also showed elevated rates of ASD-related personality traits. In contrast, PM carriers performed similarly to controls on social-cognitive tasks that involved reliance on faces and biological motion. The PM group did not differ from controls on self-reported depression or anxiety symptoms. Using latent profile analysis, we observed three distinct subgroups of PM carriers who varied considerably in their performance across tasks. Among PM carriers, CGG repeat length was a significant predictor of pragmatic language violations. Results suggest a nuanced phenotypic profile characterized by subtle differences in select clinical-behavioral, social-cognitive, and executive abilities associated with the FMR1 PM in women.